Tools to Image Germplasm Dynamics During Early Zebrafish Development - Zaucker, Andreas; Mitchell, Claire A.; Coker, Helena L. E.; Sampath, Karuna (Frontiers in Cell and Developmental Biology, 2021)
During the first day of zebrafish development, ribonucleoprotein (RNP) complexes called germplasm form large aggregates that initially segregate asymmetrically during cleavage stages. After zygotic genome activation, the granules break into smaller fragments that associate with the nuclear membrane as perinuclear (germ) granules towards the end of gastrulation. The mechanisms underlying the highly dynamic behavior of germ granules are not well studied but thought to be facilitated by the cytoskeleton. Here, we present efficient mounting strategies using 3d-printed tools that generate wells on agarose-coated sample holders to allow high-resolution imaging of multiplexed embryos that are less than one day post-fertilization (dpf) on inverted (spinning disk confocal) as well as upright (lattice light-sheet and diSPIM) microscopes. In particular, our tools and methodology allow water dipping lenses to have direct access to mounted embryos, with no obstructions to the light path (e.g., through low melting agarose or methyl cellulose). Moreover, the multiplexed tight arrays of wells generated by our tools facilitate efficient mounting of early embryos (including cleavage stages) for live imaging. These methods and tools, together with new transgenic reporter lines, can facilitate the study of germ granule dynamics throughout their lifetime in detail, at high resolution and throughput, using live imaging technologies.